PENGARUH PENGELOLAAN HARTA WAKAF TERHADAP KESEJAHTERAAN MASYARAKAT DI DESA SELOK ACEH KECAMATAN SINGKIL - Fitri Radasari; Ahmad Adib Nasution; Syamsul Effendi (MUTLAQAH: Jurnal Kajian Ekonomi Syariah, 2022)
Waqf is an important institution in Islamic teachings, the management of waqf property is a strategic step to develop the assets of the ummah for the economic prosperity of the Islamic ummah. In Law No. 41 of 2004, various forms of rules for managing waqf assets are explained and reaffirmed by government regulation No. 42 of 2006 which clearly prioritizes the management of waqf assets. This study aims, firstly, to determine the management of waqf assets that occurred in Selok Aceh Village, Singkil District, secondly, to determine Nazir's position in the management of waqf assets, and thirdly, to find out the facts that support and hinder the management of waqf assets. This research is a quantitative research. The place and location that is the object of this research is in Selok Aceh Village, Singkil District. Data sources are classified into two, namely primary which includes field studies by conducting direct interviews related to the management of waqf assets, while secondary data in the form of books, journals and others related to waqf. Data analysis uses four steps, first data collection, second data reduction, third data exposure, fourth conclusion. The results of this study conclude that the management of waqf assets in Selok Aceh Village, Singkil District has not been maximized because the abandoned waqf assets have not been developed and have not been preserved in the sense that they have not been certified